The Significance of Black Panther Activism In 1960’s for 21st Century American Audience: A Representation Study On Rita Gracia’s One Crazy Summer - Azimatul Lutvy Bellina (Fakultas Ilmu Budaya, 2024)
This study aims to investigate the interconnection of the discourse of activism between the Black Panther party in 1968 as represented in One Crazy Summer and Black Lives Matter in 21st century. Highlighting the issues of racism, the dissemination of information as the movement formation, and the resulting outcomes. This study focuses on how the discourse of activism was shaped by the protagonist and the surrounding environment in order to properly represent the genuine nature of black activism. The descriptive qualitative method is used regarding the textual data. Hall’s representation theory assisted by Foucault’s Discursive approach is used to analysed how power-knowledge structure construct the discourse of black activism, and to exposes the author’s critical position. The analysis technique is start by studying the narratives of characters Delphine, Vonneta, and Fern regarding their involvement within the Black Panther activism in Oakland, 1968. Thus, navigating the discourse of activism as represented into Black Lives Matter activism in 21st century. The finding of the research shows that the novel's portrayal of BPP’s activism mirrors the relationships surrounding the formation of the movement and the outcomes of the contemporary Black Lives Matter movement in 2013. Thus, provide a comparative analysis across two timelines of black activism. Rita encourages the readers to learn history and take awareness of race struggles issues todays.
Reuploud file repositori 26 Jan 2026_Firli
Keywords: Representation Theory; Activism; Black Panther Party; Black Lives Matter